(NfINANSY sssr (B:s (Nu^EBNOE POSOBIE (B/s - (NbOLDYREW(B, (Nb(B.(Ng(B.s; d; (NsY^EW(B, (Nn(B.(Ng(B.s ((NmOSKWA (B:s (NfINANSY(B,s, 1979)
(NaLF(B.-(NPREDM(B. (NUKAZ(B.: (NS(B. 270 - 274s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NfINANSYs